Analisis Determinan Tingkat Pengangguran di Kab Langkat - Aidila Syafitri; Yusrizal Yusrizal; Khairina Tambunan (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to analyze the determinants of the unemployment rate in Langkat Regency. The research method used is a quantitative method with the OLS (Ordinary Least Square) method. This shows that the variables Inflation, Economic Growth and Wage Level can explain the unemployment rate in Langkat Regency of 61.3% with the remaining 38.7% which will be explained by other factors. From the results of the partial significance test which were analyzed, the t-count of inflation was 0.125583 > 2.00665. It can be concluded that inflation significantly influences the unemployment rate in Langkat Regency. Meanwhile, for the Economic Growth variable, the calculated t value was -0.453940 < 2.00665, so it can be concluded that the Economic Growth variable does not significantly influence unemployment in Langkat Regency. Meanwhile, for the Wage Level variable, the calculated t value was 0.394292 > 2.00665, so it can be concluded that the Wage Level significantly influences the unemployment rate in Langkat Regency. Meanwhile, from the results of the simultaneous significant test, a value of 0.613873 > 3.59 can be obtained and it can also be seen that the probability value is smaller than the significance (α) of 5% or 0.000174 < 0.05, it can be concluded that Inflation , Economic Growth (GDP) and Wage Levels together (simultaneously) can influence the unemployment rate in Langkat Regency.